Trends in opioid and nonsteroidal anti-inflammatory (NSAID) usage in children undergoing common urinary tract reconstruction: A large, single-institutional analysis. Issue 4 (August 2022) - Mittal, Sameer; Eftekharzadeh, Sahar; Aghababian, Aznive; Shah, Jay; Fischer, Katherine; Weaver, John; Tan, Connie; Plachter, Natalie; Long, Christopher; Weiss, Dana; Zaontz, Mark; Kolon, Thomas; et al.
Summary: Introduction and objective: Opioid stewardship is recognized as a critical clinical priority. We previously reported marked reductions in narcotic administration after implementation of an opioid reduction protocol for pediatric ambulatory urologic surgery. We hypothesize that a decrease in post-operative and discharge opioid administration will not increase short-term adverse events. Study design: All pediatric patients undergoing open or robot-assisted laparoscopic pyeloplasty or ureteral reimplantation between 2015 and 2019 were included. Patients' demographics, opioid and NSAID administration, urology or pain-related emergency department (ED) visits, readmissions, and reoperations within 30 days of surgery, were aggregated. Results: 438 patients, with a median age of 3.5 years (IQR 1.5–8.3) at the time of surgery, met the inclusion criteria. Annual rates of inpatient opioid administration and prescriptions decreased significantly over the study period, while rates of intra-operative, inpatient, and prescribed NSAIDs significantly increased. There was no significant difference in the occurrence of ED visits, readmissions, or reoperations within 30 days of surgery between patients who received an opioid prescription and those who did not. Multivariate regression showed that patients who did not receive an opioid prescription at discharge were found to be at a lower risk for unplanned encounters including ED visits, readmissions, or reoperations (OR:0.5, 95%CI: 0.2–0.9, p = 0.04). Discussion: The present study shows the decreasing trend in inpatient opioid administration and opioid prescription after discharge, when accompanied by an increase NSAID administration, does not result in a significant change in rates of unplanned encounters and complications, similar to results from previous studies on non-urological and ambulatory urological surgeries. Conclusions: Non-opioid pain control after major pediatric urologic reconstruction is safe and effective. We found that a reduction in opioid administration can be associated with a reduced risk of unplanned ED visits, readmissions, or reoperations. Further investigations are required to corroborate this finding. Summary Figure Summary Figure